International Comparative Study : Engineering Education in India - World Bank (Washington, DC, 2014)
The central and state governments of India have been pursuing several reforms in the higher education sector. In engineering education, the government has already embarked on several reforms within the current legislative framework. Given this dynamic momentum, the engineering education sector in India is expected to receive a significant boost over the next few years. It is therefore timely to take stock and review the position of the sector internationally. This study thus aims to provide the Ministry of Human Resource Development (MHRD), the All India Council for Technical Education (AICTE), and relevant stakeholders with key facts, reliable data, and the results of relevant international comparisons to establish a common ground and to help in measuring the performance of the current engineering education system in India. The government also recognizes the importance of lessons that may be learned from the other Brazil, the Russian Federation, India, and China (BRIC) countries, and these countries were therefore selected for the comparison. This report is organized as follows: section one gives introduction; section two briefly discusses the background of both general higher education and engineering education in India. Section three reviews earlier comparative studies on international engineering education. Section four describes the scope of the study. Section five explains the methodology of data collection and identifies the data sources. Section six outlines the analysis of the collected data and the findings. Section seven presents conclusions. The appendixes describe the engineering education systems of the various countries examined in the study, the related challenges and opportunities, and the future policy goals in each country.